Speaker-recognition ability of blind and sighted subjects - Braun, Almut (International Journal of Speech, Language and the Law, 2012)
Blind individuals are known to outperform sighted ones in a variety of auditory tasks. The present study was carried out to investigate whether the blind possess superior speaker-recognition abilities as well. Approximately one week after subjects were familiarised with the voice of one speaker, they had to recognise him among seven matched foils within two voice line-ups (hi-fi vs cellular telephone quality). As a result, the blind performed significantly better than the sighted under hi-fi condition (p